The effectiveness of Sodium Benzoate as corrosion inhibitor for stainless steel in seawater environment - H. B., Senin; S.Y., Seoh; Mohammed Misbahul, Amin (University College of Science and Technology Malaysia, 2009)
The inhibitive properties of sodium benzoate for stainless steel controlling corrosion have been studied in seawater at room temperature. Three sets of sample have been prepared with the concentrations of 0.3M, 0.6M and 1.0M of sodium benzoate, respectively. One set of sample has been prepared without adding any sodium benzoate. This is to enable a comparison of the inhibited environment's rate of corrosion to be made. It was found that the highest corrosion rate was observed for the stainless steel with no inhibitor was added to the seawater. The corrosion rate decreases as the concentration of sodium benzoate being increased. Results have shown that by the addition of 1.0M of sodium benzoate in seawater samples, is giving > 90% efficiencies.